2017
DOI: 10.2196/preprints.9200
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patient Adherence to Scheduled Vital Sign Measurements During Home Telemonitoring: Analysis of the Intervention Arm in a Before and After Trial (Preprint)

Abstract: Background This paper presents findings on patient compliance with scheduled vital signs measurements in the recently completed Commonwealth Scientific and Industrial Research Organization (CSIRO) national trial of home telemonitoring of patients with chronic conditions, carried out at five locations along the east coast of Australia. ObjectivesTo investigate the ability of chronically ill patients to carry out a daily schedule of vital signs measurements as part of a chronic disease management care plan, over… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In addition, participants’ opinions regarding the use of the comment section were divided; some would write extensively, while others hesitated as it would lead to an immediate follow-up call from the telenurse. The extensiveness of the questionnaires and its response frequency of patients warrant discussion, however, evidence exists that patients using telemonitoring services prefer a 2 to 3 day per week response rate [ 33 , 34 ]; allowing for increased autonomy and adherence to lifelong chronic disease management. Although patient preferences must be considered when standardizing the clinical telemonitoring protocols, several participants expressed no reluctance and instead encouraged sharing their personal data with the clinical team across levels of care.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, participants’ opinions regarding the use of the comment section were divided; some would write extensively, while others hesitated as it would lead to an immediate follow-up call from the telenurse. The extensiveness of the questionnaires and its response frequency of patients warrant discussion, however, evidence exists that patients using telemonitoring services prefer a 2 to 3 day per week response rate [ 33 , 34 ]; allowing for increased autonomy and adherence to lifelong chronic disease management. Although patient preferences must be considered when standardizing the clinical telemonitoring protocols, several participants expressed no reluctance and instead encouraged sharing their personal data with the clinical team across levels of care.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, participants' opinions regarding the use of the comment section were divided; some would write extensively, while others hesitated as it would lead to an immediate follow-up call from the telenurse. The extensiveness of the questionnaires and its response frequency of patients warrant discussion, however, evidence exists that patients using telemonitoring services prefer a 2 to 3 day per week response rate; 35,36 allowing for increased autonomy and adherence to lifelong chronic disease management. Although patient preferences must be considered when standardizing the clinical telemonitoring protocols, several participants expressed no reluctance and instead encouraged sharing their personal data with the clinical team across levels of care.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found varying adherence rates, typically between 40% and 90%, to TM in HF [47,60,61]. Another study found that the average adherence rate to BP monitoring and blood sugar monitoring was 59.7% and 50.2%, respectively [61]. In addition, other previous studies have found an initial drop in patient adherence during onboarding, followed by a steadier adherence rate over time [47,48,60].…”
Section: Adherence To Tm In Cccsmentioning
confidence: 96%
“…The results indicated an average adherence rate of 77.2% (142/184) in HF monitoring, 55% (29/52) in HTN monitoring, and 72% (19/26) in DM monitoring. Previous research has found varying adherence rates, typically between 40% and 90%, to TM in HF [47,60,61]. Another study found that the average adherence rate to BP monitoring and blood sugar monitoring was 59.7% and 50.2%, respectively [61].…”
Section: Adherence To Tm In Cccsmentioning
confidence: 97%